2012
DOI: 10.1016/j.ijforecast.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of linear regression and survival analysis using single and mixture distributions approaches in modelling LGD

Abstract: Estimating Recovery Rate and Recovery Amount has become important in consumer credit because of the new Basel Accord regulation and because of the increase in number of defaulters due to the recession. We compare linear regression and survival analysis models for modelling Recovery rates and Recovery amounts, so as to predict Loss Given Default (LGD) for unsecured consumer loans or credit cards. We also look at the advantages and disadvantages of using single distribution models or mixture distribution models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 12 publications
(12 reference statements)
1
37
0
Order By: Relevance
“…For a full overview on AFT models and more technical details we refer to Collett (2003) and Kleinbaum and Klein (2011). AFT models are used in the credit risk context by Narain (1992) (who used an exponential distribution), Banasik et al (1999) (who used exponential and Weibull distributions) and Zhang and Thomas (2012) Using the relationship r ¼ 1 p , it can be shown that a Weibull-distributed random event time T i ¼ expðb 0 x i þ r i Þ corresponds to a survival function…”
Section: Survival Analysis Methodsmentioning
confidence: 99%
“…For a full overview on AFT models and more technical details we refer to Collett (2003) and Kleinbaum and Klein (2011). AFT models are used in the credit risk context by Narain (1992) (who used an exponential distribution), Banasik et al (1999) (who used exponential and Weibull distributions) and Zhang and Thomas (2012) Using the relationship r ¼ 1 p , it can be shown that a Weibull-distributed random event time T i ¼ expðb 0 x i þ r i Þ corresponds to a survival function…”
Section: Survival Analysis Methodsmentioning
confidence: 99%
“…For a full overview on AFT models and more technical details we refer to Collett (2003) and Kleinbaum and Klein (2011). AFT models are used in the credit risk context by Narain (1992) (who used an exponential distribution), Banasik et al (1999) (who used exponential and Weibull distributions) and Zhang and Thomas (2012) (who used Weibull, log-logistic and gamma distributions). Using the relationship r ¼ 1 p , it can be shown that a Weibull-distributed random event time…”
Section: Survival Analysis Methodsmentioning
confidence: 99%
“…With a high amount of censoring, mean values of these survival analyses do not give good predictors. Zhang and Thomas (2012) compute a predictor for the recovery rate in survival analysis by looking at each percentile of the training set and calculate the squared and absolute deviations from the predictions to the observed values of the default cases. Next, the percentiles resulting in the lowest deviations are withheld and used to compute the deviations in the test set.…”
Section: Evaluation Through Default Time Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…CART can be used to analyse either quantitative or categorical data and is widely used in building scoring models (e.g. [10,13,16,32,39,59,60] ).…”
Section: Related Studiesmentioning
confidence: 99%